Early (N170/M170) Face-Sensitivity Despite Right Lateral Occipital Brain Damage in Acquired Prosopagnosia - Alonso Prieto, Esther; Caharel, Stephanie; Henson, Richard N.; Rossion, Bruno (Frontiers in Human Neuroscience, 2011)
Compared to objects, pictures of faces elicit a larger early electromagnetic response at occipito-temporal sites on the human scalp, with an onset of 130 ms and a peak at about 170 ms. This N170 face effect is larger in the right than the left hemisphere and has been associated with the early categorization of the stimulus as a face. Here we tested whether this effect can be observed in the absence of some of the visual areas showing a preferential response to faces as typically identified in neuroimaging. Event related potentials were recorded in response to faces, cars and their phase-scrambled versions in a well-known brain-damaged case of prosopagnosia (PS). Despite the patient’s right inferior occipital gyrus lesion encompassing the most posterior cortical area showing preferential response to faces (“occipital face area”, OFA), we identified an early face-sensitive component over the right occipito-temporal hemisphere of the patient that was identified as the N170. A second experiment supported this conclusion, showing the typical N170 increase of latency and amplitude in response to inverted faces. In contrast, there was no N170 in the left hemisphere, where PS has a lesion to the middle fusiform gyrus and shows no evidence of face-preferential response in neuroimaging (no left “fusiform face area”, or lFFA). These results were replicated by a magneto-encephalographic (MEG) investigation of the patient, disclosing a M170 component only in the right hemisphere. These observations indicate that face preferential activation in the inferior occipital cortex is not necessary to elicit early visual responses associated with face perception (N170/M170) on the human scalp. These results further suggest that when the right inferior occipital cortex is damaged, the integrity of the middle fusiform gyrus and/or the superior temporal sulcus – two areas showing face preferential responses in the patient’s right hemisphere - might be necessary to generate the N170 effect.